2013
DOI: 10.1159/000351028
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Slipped Capital Femoral Epiphysis in Children Undergoing Gonadotropin-Releasing Hormone Agonist Therapy for the Treatment of Central Precocious Puberty

Abstract: Background: Obesity, age and hormone imbalances including hypothyroidism and growth hormone deficiency and therapy, but not gonadotropin-releasing hormone agonist (GnRHa) therapy, have been identified as risk factors for slipped capital femoral epiphysis (SCFE). Five of 7 reported cases describe SCFE in children shortly after GnRHa therapy cessation. Methods: We report 3 cases of SCFE that occurred in children on GnRHa therapy for the treatment of central precocious puberty (CPP) and discuss possible promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Anaphylaxis is a serious allergic or hypersensitivity reaction that is rapid in onset and may cause life-threatening conditions 11) . SCFE is the displacement of the upper femoral epiphysis from the femoral metaphysis 10) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaphylaxis is a serious allergic or hypersensitivity reaction that is rapid in onset and may cause life-threatening conditions 11) . SCFE is the displacement of the upper femoral epiphysis from the femoral metaphysis 10) .…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, anaphylaxis may rarely occur as a systemic side effect related to GnRHa administration. Recently, there have been reports indicating that administration of GnRHa may be a risk factor for the development of slipped capital femoral epiphysis (SCFE) 7 , 8 , 9 , 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Side effects include adverse skin reactions (sometimes requiring desensitization) in the absence of immunoglobulin G (IgG) antibodies toward the drug . An uncontrolled study has suggested that slipped capital femoral epiphysis can occur in children during therapy with GnRH‐agonists, a series that included one girl with HH . The efficacy of GnRH agonists to suppress puberty associated with HH is high .…”
Section: Treatmentmentioning
confidence: 99%
“…52 An uncontrolled study has suggested that slipped capital femoral epiphysis can occur in children during therapy with GnRH-agonists, a series that included one girl with HH. 53 The efficacy of GnRH agonists to suppress puberty associated with HH is high. 54 Failures are most often caused by medication intolerance, usually local injection site reactions, which have been reported to occur in 1-8% of patients.…”
Section: Premature Thelarche Adrenarche and Pubarchementioning
confidence: 99%
“…Local effects of GnRH analogues including induration and aseptic abscess are generally well known. Rare adverse effects of the agents on the nervous system, skin, gastrointestinal tract, and cardiovascular system have also been reported (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%